Phytochemical screening, antiobesity, antidiabetic and antimicrobial assessments of Orobanche aegyptiaca from Palestine - Nidal Jaradat; Mohammad Qadi; Iyad Ali; Fatima Hussein; Linda Issa; Doaa Rashdan; Manal Jamoos; Re'as Najem; Abdulraziq Zarour; Mohammad Arar (BMC, 2021)
Abstract Background Microbial resistance, diabetes mellitus, and obesity are global health care problems that have posed a serious threat to both human and environmental ecosystems. The goals of the present investigations are to investigate the phytoconstituents, antilipase, anti-α-amylase, and antimicrobial activity of Orobanche aegyptiaca Pers. (OA) from Palestine. Methods Identification of the phytoconstituents of OA plant petroleum ether, methylene chloride, chloroform, acetone, and methanol extracts were conducted using pharmacopeia's methods, while porcine pancreatic lipase and α-amylase inhibitory activities were examined using p-nitrophenyl butyrate and 3,5-dinitro salicylic acid methods, respectively. Moreover, the antimicrobial activity was evaluated utilizing broth microdilution assay against eight bacterial and fungal strains. Results The phytochemical screening results showed that the methanol extract of the OA plant is rich in phytochemical components, also this extract has powerful antilipase potential with an IC50 value of 19.49 ± 0.16 μg/ml comparing with the positive control (Orlistat) which has antilipase activity with IC50 value of 12.3 ± 0.35 μg/ml. Moreover, the methanol and chloroform extracts have powerful α-amylase inhibitory activity with IC50 values of 28.18 ± 0.22 and 28.18 ± 1.22 μg/ml, respectively comparing with Acarbose which has α-amylase inhibitory activity with IC50 dose of 26.3.18 ± 0.28 μg/ml. The antibacterial results showed that the methylene chloride extract exhibited the highest antibacterial activity among the other OA plant extracts with a MIC value of 0.78 mg/ml against S. aureus, while, the methylene chloride, petroleum ether, and chloroform extracts of the OA plant showed potential antifungal activity against C. albicans strains with MIC value of 0.78 mg/ml. Conclusion The OA methanol and chloroform extracts could be excellent candidates as antilipase and anti-α-amylase bioactive materials. In addition, methylene chloride, petroleum ether, and chloroform extracts could be potential natural antimicrobial products.